2023
DOI: 10.3389/fphar.2023.1226448
|View full text |Cite
|
Sign up to set email alerts
|

Inulin ameliorates metabolic syndrome in high-fat diet-fed mice by regulating gut microbiota and bile acid excretion

Abstract: Background: Inulin is a natural plant extract that improves metabolic syndrome by modulating the gut microbiota. Changes in the gut microbiota may affect intestinal bile acids. We suggest that inulin may improve metabolism by inducing bile acid excretion by gut microbes.Methods: Male C57/BL mice were fed either a high-fat diet (60% calories) or a regular diet for 16 weeks, with oral inulin (10% w/w). At the end of the experiment, the gene expression levels (FGF15, CD36, Srebp-1c, FASN, and ACC) in the liver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Li found that fructooligosaccharide down-regulated the levels of the SREBPs and ChREBP in mice fed a high sucrose diet [34]. Huang et al noted that inulin reduced the gene expression of CHREBP, SREBP-1C, and FASN in mice fed a high-fat diet [35]. These findings align with our research, suggesting that dietary fiber possesses the ability to inhibit hepatic lipid synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…Li found that fructooligosaccharide down-regulated the levels of the SREBPs and ChREBP in mice fed a high sucrose diet [34]. Huang et al noted that inulin reduced the gene expression of CHREBP, SREBP-1C, and FASN in mice fed a high-fat diet [35]. These findings align with our research, suggesting that dietary fiber possesses the ability to inhibit hepatic lipid synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…This was also observed when Komatsu et al reported that 28 days of a high-inulin diet (20% w/w) did not induce statistically significant changes to systemic IL-6, triglyceride, and HDL levels compared to control diet (5% w/w) in DahlS.Z-Lepr fa /Lepr fa (DS/obese) rats [47]. However, a longer 16-week study on HFD-fed (60% of their diet in terms of calories) C57/BL mice supplemented with inulin (10% w/w) found significantly (p < 0.05) lower serum triglyceride, TNF-a, and Il-6 levels, whilst HDL levels remained unchanged [48]. An HFD has been linked to inflammation via a phenomenon termed 'metabolic endotoxemia' [49].…”
Section: Metabolic and Inflammatory Biomarker Responses To Inulin Sup...mentioning
confidence: 99%